FLUCTUATIONS IN OIL PRICES AND THEIR IMPACT ON SOME VARIABLES OF FISCAL POLICY IRAQ AS A MODEL FOR PERIOD (2004- 2017) - Thijel Jawad, Haidar; Hassan Rasham, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
The major challenge faced by the oil countries, including Iraq, is the changes and fluctuations in the prices of crude oil and their financial returns, which is reflected negatively on the development processes in these countries as they depend on the development of oil revenues. The research aims at shedding light on the importance and role of the oil sector in the Iraqi economy and its impact on the changes in the fiscal policy in Iraq and its role in achieving balance and economic stability. The research has reached a number of results, the most important of which is that one of the biggest challenges facing the Iraqi economy is the large dependence on the oil sector, which leads to fluctuation of public revenues due to fluctuations in oil prices leading to financial instability in Iraq, which leads to a deficit in the general budget being Depends almost entirely on the revenues of the oil sector and recommends the research the need to develop development plans by the competent authorities in order to support the variables of fiscal policy to achieve balance and economic stability and avoid shocks in the prices of crude oil.